2016
DOI: 10.5937/industrija44-9572
|View full text |Cite
|
Sign up to set email alerts
|

The effects of economic activities diversification on development: The perspective of Serbia

Abstract: Each economy specializes in certain economic activities depending on the development level and availability of resources. During their development, countries undergo sectoral transformation. In order to achieve a higher level of economic development, it is necessary for a country to diversify

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…This underscores the importance of promoting export diversification strategies to stimulate economic growth in E-7 countries. These results are consistent with other studies by Sadorsky (2012), Jednak et al (2016), andMcIntyre et al (2018), which highlight the positive connection between economic growth and export diversification. Based on the findings, it is clear that E-7 countries have to remove barriers to foreign trade to attain better levels of economic growth.…”
Section: Pooled Mean Group Autoregressive Distributed Lag (Pmg-ardl) ...supporting
confidence: 93%
See 1 more Smart Citation
“…This underscores the importance of promoting export diversification strategies to stimulate economic growth in E-7 countries. These results are consistent with other studies by Sadorsky (2012), Jednak et al (2016), andMcIntyre et al (2018), which highlight the positive connection between economic growth and export diversification. Based on the findings, it is clear that E-7 countries have to remove barriers to foreign trade to attain better levels of economic growth.…”
Section: Pooled Mean Group Autoregressive Distributed Lag (Pmg-ardl) ...supporting
confidence: 93%
“…This diversification and expansion provide the stability, security, and dependability that emerging countries require rather than relying largely on the production of primary goods, which is typically unpredictable and vulnerable to fluctuations (Abu Wadi and Bashayreh, 2018). Jednak et al (2016) investigated the effects of economic diversification on Serbia's development from 2007 to 2012. They discovered that the structure and diversification of economic activities promote economic growth and development.…”
Section: Nexus Between Export Diversification and Economic Growthmentioning
confidence: 99%
“…Keller and Nabli (2002) indicates that there is a limited effect of technology development on growth in gulf countries because they import technology and high quality workers besides the low expending on research and development. Jednak et al (2016), they investigate the impact of economic diversification on the development of Serbia over the period (2007)(2008)(2009)(2010)(2011)(2012). They found that economic activities structure and diversification have a positive influence on economic growth and development.…”
Section: The Gcc Economic Diversification Overview and Literature Reviewmentioning
confidence: 99%
“…The foreign capital inflow decreased from 14.3% to 5.6% GDP (in 2009) and the slower pace of credit activities has resulted in a drop in production, income, personal consumption, and consequently in the drop in domestic demand (about 7%). For all these reasons, the Government of Serbia has changed its strategies for economic growth and development (Jednak et al, 2013).…”
Section: Overview Of Serbian Economic Growth and Development Strategiesmentioning
confidence: 99%